1985
DOI: 10.1021/bi00341a028
|View full text |Cite
|
Sign up to set email alerts
|

Local base dynamics and local structural features in RNA and DNA duplexes

Abstract: Local base motion and local structural base information are derived with a simple motional model from site specifically spin-labeled polyribo- and polydeoxyribonucleotides. The model was developed earlier for some nucleic acids and has now been applied to analyze 22 different nucleic acid systems. We conclude that the base motion of the spin-labeled nucleotide in single-stranded RNA, DNA, or non-base-paired bases in duplexes is of the order of 1 ns and that its base mobility decreases by about a factor of 4 up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 24 publications
4
40
1
1
Order By: Relevance
“…The results clearly demonstrated spectral divergence, where different RNA elements, such as single-stranded U, stacked A/U pair, and U/U mismatch, give different EPR lineshapes. This further strengthens the notion that SDSL is capable of detecting site-specific RNA structural features [9][10][11][12][13][14][15][16]. The data also revealed that the stacked A/U pair spectrum in the SDR shows the same characteristic feature to that observed in a different molecule.…”
Section: Discussion Towards the First Sdsl Lineshape Library For Rnasupporting
confidence: 82%
See 2 more Smart Citations
“…The results clearly demonstrated spectral divergence, where different RNA elements, such as single-stranded U, stacked A/U pair, and U/U mismatch, give different EPR lineshapes. This further strengthens the notion that SDSL is capable of detecting site-specific RNA structural features [9][10][11][12][13][14][15][16]. The data also revealed that the stacked A/U pair spectrum in the SDR shows the same characteristic feature to that observed in a different molecule.…”
Section: Discussion Towards the First Sdsl Lineshape Library For Rnasupporting
confidence: 82%
“…SDSL utilizes a site-specifically attached nitroxide moiety that contains a stable, unpaired electron, and obtains local structural information by analyzing the electron paramagnetic resonance (EPR) spectrum of the nitroxide [8]. It is capable of providing information on high molecular weight assemblies under physiological conditions using a small amount of sample (∼5 μl of 50 μM of sample per measurement), and has been utilized to monitor solution structure and conformational changes at specific sites of RNA molecules [9][10][11][12][13][14][15][16] and to measure distances between two labeled sites within RNAs [17][18][19][20].An important source of information in RNA SDSL is the spectral lineshape of a singly labeled nitroxide [7]. In the conventional X-band measurements, the observed lineshape changes…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under such conditions, one determines an ESR lineshape for the spin-labeled viral DNA which is characteristic for a double-stranded B-DNA system. The ESR spectrum is similar to that determined for (A,-T,, opip5U,), [4] or (opip'U,, Td)n-(A,)" [9]. For comparative purposes, the experimental and computer-simulated ESR spectra of (opip5U,, T,)".…”
Section: I)supporting
confidence: 63%
“…Through nuclear magnetic resonance (NMR) studies [2], it has been shown that, inside an intact double helix, the deoxyribose and the sugar-phosphate backbone fluctuate from their equilibrium geometry, and bases undergo libration motions with correlation times of the order of nanoseconds or longer. Electronic spin resonance measurements [3] have revealed the existence of base motions on the nanosecond timescale in RNA and DNA single-and double-stranded systems. In addition, fast conformational motions in the picosecond and nanosecond time-window, already revealed by molecular dynamics (MD) [4,5] and time-resolved fluorescence depolarization [6] measurements, seem to be crucial in many functionally important processes such as chemical reactions involving local interactions with the reacting site and sequences recognition by enzymes [7].…”
Section: Introductionmentioning
confidence: 99%